An Egyptian Mummy of the Late Old Kingdom in the Michael C. Carlos Museum, Emory University - Lacovara, Peter.
This article discusses the history, importance, and conservation treatment of an Egyptian Old Kingdom mummy, purchased from the site of Abydos in 1920. It is the oldest, substantially intact, mummy of this date in the Americas.